CHALLENGES OF INTEGRATING TECHNOLOGY IN TEACHING MATHEMATICS IN PRIMARY SCHOOL: PERSPECTIVES FROM TEACHERS IN AWKA SOUTH LOCAL GOVERNMENT EDUCATION AUTHORITY - OKEKE, Eucharia Nneka; OKEKE, Goodness Chukwuemeka; OBIDIKE, Ngozi Diwunma (Journal of Early Childhood and Primary Education, 2025)
The integration of technology into primary school mathematics teaching presents numerous challenges for teachers. Despite the potential benefits of technology in enhancing mathematics instruction, teachers face significant obstacles in its implementation. This study aims to identify and analyse the specific challenges teachers encounter when integrating technology into primary school mathematics lessons. Two research questions guided the study. A survey research design was adopted for the study. A 30-item questionnaire titled Challenges of Integrating Technology in Primary School Mathematics Teaching (CITPSMT), was validated by three experts and pilot-tested (Cronbach’s α = 0.79–0.85), was used for data collection. The population of study was 1440 teachers in the 45 primary schools in Awka South Local Government Education Authority. The sample was 150 teachers randomly drawn from primary schools in Awka South LGEA. Mean and standard deviation were used to analyse the data collected. The study revealed that teachers struggle with issues related to insufficient training, lack of resources, and difficulties in aligning technology with curriculum standards. These findings highlight the need for targeted professional development and increased investment in technological resources to support teachers in effectively integrating technology into their mathematics teaching. It was recommended among others that schools should invest in comprehensive professional development programs that address both the technical and pedagogical aspects of technology use and adequate digital tools should be provided to schools by the government.
Keywords: Technology Integration; Mathematics Teaching; Primary Education; Teaching Challenges